Antioxidant property of anthocyanin from Malatinta (Phyllanthus reticulatus Poir.) fruits obtained by static and microwave-assissted extraction. - Baldonasa, RB Hera Angelica R. (2015.)
Fresh fruits of Phyllanthus reticulatus Poir. were analyzed for anthocyanin by spectrophotometric method. The antioxidant activity using 1,1-diphenyl-2picrylhydrazyl (DPPH) free radical scavenging activity (FRSA) and reducing power (RP) through FeCl3 assay were determined. The use of two extraction processes, namely, the static method and microwave-assisted extraction, using two extraction solvents, acidified methanol and aqueous ethanol (1;1) were compared., The total anthocyanin content (TAC) of P. reticulatus fruit was highest in extract using static method of extraction in acidified methanol solvent (279.94+-17.31 mg/100g), comparable to levels found in plants rich in anthocyanins. (e.g., berries genotypes, grapes and red cabbages). In microwave-assisted extraction, TAC using acidified methanol was higher (278.01 +- 18.76 mg/100g) compared to using aqueous ethanol (210.96 +- 2.02 mg/100g). P. reticulatus fruits exhibited high antioxidant activity as revealed by its RP and DPPH FRSA results when compared to ascorbic acid. These findings highlight the usefulness of P. reticulatus as a source of anthocyanins with good antioxidant properties, which, in turn, gives importance to the undervalued and underutilized plant.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Malatinta -- Anthocyanin; Phyllanthus reticulatus Poir